2008
DOI: 10.1534/genetics.107.083535
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Dissociation of Nonhomologous End Joining Proteins at a DNA Double-Strand Break in Saccharomyces cerevisiae

Abstract: Nonhomologous end joining (NHEJ) is an important DNA double-strand-break (DSB) repair pathway that requires three protein complexes in Saccharomyces cerevisiae: the Ku heterodimer (Yku70-Yku80), MRX (Mre11-Rad50-Xrs2), and DNA ligase IV (Dnl4-Lif1), as well as the ligase-associated protein Nej1. Here we use chromatin immunoprecipitation from yeast to dissect the recruitment and release of these protein complexes at HO-endonuclease-induced DSBs undergoing productive NHEJ. Results revealed that Ku and MRX assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(171 citation statements)
references
References 68 publications
11
156
1
3
Order By: Relevance
“…5C), suggesting that interactions with both yKu and Nej1 contribute to enhanced DNA binding by Dnl4-Lif1. Our data and other published studies (19,24) are consistent with a model in which yKu initiates binding at a DSB and then independently recruits Nej1 and Dnl4-Lif1. To mimic this scenario, we examined the effect of mixing Nej1 and Dnl4-Lif1 prior to loading onto DNA bound by yKu.…”
Section: Journal Of Biological Chemistry 4935supporting
confidence: 92%
See 2 more Smart Citations
“…5C), suggesting that interactions with both yKu and Nej1 contribute to enhanced DNA binding by Dnl4-Lif1. Our data and other published studies (19,24) are consistent with a model in which yKu initiates binding at a DSB and then independently recruits Nej1 and Dnl4-Lif1. To mimic this scenario, we examined the effect of mixing Nej1 and Dnl4-Lif1 prior to loading onto DNA bound by yKu.…”
Section: Journal Of Biological Chemistry 4935supporting
confidence: 92%
“…Vivo DSBs-Although Nej1 is a direct participant in yeast NHEJ (24), the mechanisms by which it contributes to NHEJ are not well defined. In accord with published studies (20 -23), deletion of NEJ1 in the SLY1 genetic background resulted in a defect in NHEJ, measured either by growth when HO endonuclease was constitutively expressed (Fig.…”
Section: Nej1 Is Recruited By and Stabilizes The Binding Of Yku To Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The HO(12) suicide deletion strain YW1276 [MATa-inc, ade2THOSD(11) TSTE3-MET15, his3D1, leu2D, met15D, ura3D] was previously described . The chromatin immunoprecipitation (ChIP) strain YW1752 (MATa-incTChIP-QPCRT URA3, can1DTrepair-QPCR, DNL4-Myc13THisMX6, gal1T HOcsTHOcod, his3D1, leu2D0, met15D0, ura3D) was previously described (Wu et al 2008). Both YW1276 and YW1752 are direct descendants of BY4741/BY4742.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic experiments in yeast have shown that Ku occludes DNA ends from Exo1. Ku and MRX/MRN are among the first proteins recruited to DSBs (91,92). Importantly, the MRX nuclease activity and Sae2 (orthologous to CtIP) function in conjunction to remove Ku (92)(93)(94)(95).…”
Section: Removal Of Ku From Dsb Endsmentioning
confidence: 99%